2021
DOI: 10.1002/da.23144
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of early adverse stress to complex and severe depression in depressed outpatients

Abstract: Background To assess whether linear effects or threshold effects best describe the association between early adverse stress (EAS) and complex and severe depression (i.e., depression with treatment resistance, psychotic symptoms, and/or suicidal ideation), and to examine the attributable risk of complex and severe depression associated with EAS. Methods A cross‐sectional study was conducted using deidentified clinical data (on demographics, presence of complex and severe depression, and exposure to seven types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Meanwhile, not all victims develop PTSD following trauma; some may suffer disturbances in daily functioning but gradually return to normal, while other people maintain clinically significant psychological comorbidities such as anxiety and depression which require prolonged intervention (Briere, 2004; Hill, 2003). Previous research has observed that ACEs are widely common in individuals suffering from high severity of depression symptoms (Bellis et al, 2014; Gloger et al, 2021; Nelson et al, 2017). Likewise, the association between higher exposure to ACEs and higher severity of anxiety and depression symptoms in adolescent samples (Gloger et al, 2021; Goldenson et al, 2020; Waikamp & Serralta, 2018) is consistent in several studies in European, North American, Asian, and Latin American samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, not all victims develop PTSD following trauma; some may suffer disturbances in daily functioning but gradually return to normal, while other people maintain clinically significant psychological comorbidities such as anxiety and depression which require prolonged intervention (Briere, 2004; Hill, 2003). Previous research has observed that ACEs are widely common in individuals suffering from high severity of depression symptoms (Bellis et al, 2014; Gloger et al, 2021; Nelson et al, 2017). Likewise, the association between higher exposure to ACEs and higher severity of anxiety and depression symptoms in adolescent samples (Gloger et al, 2021; Goldenson et al, 2020; Waikamp & Serralta, 2018) is consistent in several studies in European, North American, Asian, and Latin American samples.…”
mentioning
confidence: 99%
“…Previous research has observed that ACEs are widely common in individuals suffering from high severity of depression symptoms (Bellis et al, 2014; Gloger et al, 2021; Nelson et al, 2017). Likewise, the association between higher exposure to ACEs and higher severity of anxiety and depression symptoms in adolescent samples (Gloger et al, 2021; Goldenson et al, 2020; Waikamp & Serralta, 2018) is consistent in several studies in European, North American, Asian, and Latin American samples.…”
mentioning
confidence: 99%
“…For the environmental conditions, several risk factors have been associated with increased risk of developing MDD and BD including, early adverse stress, psychological stressors, and drug abuse. 3–5 The combination of environmental and genetic factors may lead to intermediate phenotypes, such as altered brain gene expression and circuitry dysfunction, that affect mood disturbances. 6 These alterations may be associated with changes in different cellular pathways that culminate in inflammation, 7 , 8 decreased neuroplasticity, 9 increased oxidative stress, 10 and cell death.…”
Section: Introductionmentioning
confidence: 99%